DIGITAL FINANCE AND THE GROWTH OF THE JUA KALI ENTERPRISES IN MAKUENI COUNTY - MUTUA DANIEL MUTIE (Machakos University Press, 2025)
The aim of the study was to investigate the effect of digital finance on the growth of Jua Kali enterprises in Makueni County, Kenya, focusing on four key tools: mobile money, mobile banking, internet banking, and digital loans. The study was guided by the four specific objectives: to examine the effect of mobile money transfers on the growth of the Jua Kali enterprises in Makueni County; to assess the effect of mobile banking on the growth of the Jua Kali enterprises in Makueni County; to determine the effect of internet banking on the growth of the Jua Kali enterprises in Makueni County; and to investigate the effect of digital loans on the growth of Jua Kali enterprises in Makueni County. Anchored on the Technology Acceptance Model (TAM), Schumpeter’s Innovation Theory, Transaction Cost Theory, and Financial Inclusion Theory, the research adopted a descriptive design and employed stratified random sampling to select 266 respondents. Data were collected through structured questionnaires and analyzed using descriptive statistics, Spearman correlation, and ordinal regression analysis. The ordinal regression results revealed that mobile money had the strongest and statistically significant positive association with enterprise revenue growth (β = 1.628, Exp(β) = 5.10, p < 0.001). This indicates that enterprises utilizing mobile money were over five times more likely to achieve higher growth levels than those that did not, emphasizing its pivotal role in enhancing transaction efficiency, liquidity management, and market access within the informal sector. Digital loans also exhibited a significant positive effect (β = 0.833, Exp(β) = 2.30, p < 0.001), suggesting that access to digital credit facilities substantially improves short-term liquidity and operational performance. Similarly, internet banking had a positive and statistically significant influence (β = 0.501, Exp(β) = 1.65, p = 0.008), reflecting its growing importance in promoting financial management and supporting enterprise modernization. Conversely, mobile banking showed a positive but statistically insignificant relationship (β = 0.050, Exp(β) = 1.05, p = 0.736), implying its limited impact on growth among informal businesses, possibly due to minimal integration with enterprise financing tools. The model’s goodness-of-fit tests confirmed that the data met the proportional odds assumption, while the Nagelkerke R² value of 0.288 indicated that the digital finance variables collectively explained approximately 29% of the variation in enterprise growth levels. Overall, the findings affirm that digital financial inclusion, particularly through mobile money, internet banking, and digital lending, plays a critical role in enhancing the performance and sustainability of informal enterprises. The study concludes that strengthening Kenya’s digital finance ecosystem through innovative financial products, flexible credit systems, enhanced digital literacy, and infrastructure development is vital for promoting inclusive growth and enterprise resilience.